2016
DOI: 10.1007/s40089-016-0181-z
|View full text |Cite
|
Sign up to set email alerts
|

Phytotoxicity of Ag nanoparticles prepared by biogenic and chemical methods

Abstract: Silver nanoparticles (Ag NPs) are now widely used as antibacterial and antifungal materials in different consumer products. We report here the preparation of Ag NPs by neem leaves extract (Azadirachta) reduction and trisodium citrate-sodium borohydride reduction methods, and study of their phytotoxicity. The nanoparticles were characterized by UV-Vis spectroscopy, FTIR, and atomic force microscopy (AFM) techniques. Both neem-coated and citrate-coated Ag NPs exhibit surface plasmon around 400 nm, and their aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 22 publications
(29 reference statements)
0
16
0
Order By: Relevance
“…The colours of the samples are shown in Supporting material, Figure S5. Such a change in colour can be attributed to extended light adsorption in the visible region, [48,49] which can be the result of the presence of structural defects such as oxygen vacancies and/or interstitial Ti 3 + in the TiO 2 . [40] The catalysts were further characterised by DRUV-Vis absorbance spectra.…”
Section: Support Effect On the Electronic Interaction In The Bifunctimentioning
confidence: 99%
“…The colours of the samples are shown in Supporting material, Figure S5. Such a change in colour can be attributed to extended light adsorption in the visible region, [48,49] which can be the result of the presence of structural defects such as oxygen vacancies and/or interstitial Ti 3 + in the TiO 2 . [40] The catalysts were further characterised by DRUV-Vis absorbance spectra.…”
Section: Support Effect On the Electronic Interaction In The Bifunctimentioning
confidence: 99%
“…For example (1) less toxic and hazardous materials and environmentally benign solvents, (2) simple, rapid and cost effective, (3) consumes less energy and performs under moderate operation conditions, (4) combines the potency of both silver nanoparticles and plant active ingredients. In this respect, plant-mediated silver nanoparticles have been reported to possess more biological activities than nanoparticles synthesized by chemical methods [5].…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] The interpretation of these results is slightly modified here, in accordance with recent experimental and theoretical findings related to the variation of nanostructural properties of anatase with temperature. [26][27][28][29][30] The results of a detailed study of the most intense E g mode in the Raman spectra of anatase nanopowder synthesized by laserinduced pyrolysis, with crystallite size about 12.3 nm, are presented in the Figure 1. The spectra in the temperature range from 25 to 300 K were taken in closed cryostat coupled with Jobin Yvon U1000 macro-Raman system.…”
Section: Anatase Nanocrystalline Powdersmentioning
confidence: 99%
“…In this case PCM included not only the effects of phonon confinement and nonstoichiometry, but also the strain. Namely, recently published results have revealed that the strain in anatase particles varied with temperature [26,27,29,30] : at some medium-high temperatures, the strain could be released, but at high temperatures, close to the transformations from anatase to rutile phase, the strain could strengthen again. Also, in situ x-ray diffraction study of the anatase microstructure evolution as a function of temperature has confirmed that anatase nanoparticle size increased with temperature.…”
Section: Anatase Nanocrystalline Powdersmentioning
confidence: 99%